Perancangan Pelengkap Interior Dengan Inspirasi Interior Maroko (Studi Kasus Ruang VIP Marakez Cafe & Resto) - Yashifa Anindita Imani; Ratna Endah Santoso (Institut Seni Indonesia Surakarta, 2022)
Marakez Café & Resto is a restaurant that serves Middle Eastern specialties in Surakarta. Carrying the Café & Resto, Marakez has several spots and rooms, one of which is a VIP room provided for guests with facilities that can be considered exclusive compared to other rooms. The shape of this VIP room is actually very supportive, with a short sofa that allows customers to enjoy their food in a lesehan style, just like Middle Eastern culture, but unfortunately the interior elements in this room do not reflect the Moroccan feel as the name suggests. Based on the description that has been explained, it is necessary to design interior textile elements to build a Moroccan atmosphere because it has been supported by the shape of the room. This design uses the design method presented by Colin Clipson. The results of this design produce complementary interior styles that are based on ideas from the Moroccan interior, namely arch, zellij and mashrabiya. This design also combines two techniques in surface design, namely digital printing and embroidery, the product is an interior complement in the form of sofa upholstery, curtains and pillowcases.